Políticas públicas, o acesso ao cuidado e aos serviços de saúde e de assistência social de Campo Grande/MS: percepção da pessoa com deficiência, cuidadores e gestores - Geraldo, Juliana Pedroso Bauab (2023)
The care for the person with disability and his family is a relevant theme, due to its presence in interdisciplinary debates in national and international public policies, seeking to advance the guarantee of rights to health, social protection, accessibility, inclusion and participation in society. The general objective of this study sought to understand the perception of the person with disability, the family caregiver and the service coordinators regarding the public health and social assistance policies available in the city of Campo Grande (MS). Specifically, it aimed at the characterization of the participants and the apprehension of their perception regarding the municipal health and social assistance services and the care offered by them. This is a descriptive sectional research, qualitative in nature, covering the municipality of Campo Grande. It used data from the Municipal Census of Persons with Disabilities, between the years 2016 and 2018, for the recruitment and location of the participants. The research includes people with physical disabilities, aged between 18 and 65 years, a family caregiver of the included person with disability, and managers of municipal health and social assistance services of reference. It collected the data at home and in the services, by means of a semi-structured interview composed of characterizable items and by an initial question mobilizing verbal expression. The analysis follows the Discourse of the Collective Subject (DSC) technique. In this part, it discussed the content in the light of the scientific literature and the Theory of Social Representations. In the study, 13 people with disabilities took part, besides 8 family caregivers, 5 managers from Unidades Básicas de Saúde da Família (Basic Family Health Units) and 6 managers from Centro de Referência de Assistência Social (Reference Center for Social Assistance). It grouped and divided by thematic axes the main ideas from the speeches: service, functioning of services, infrastructure, barriers, information, organizational and financial management, support to the caregiver, professional qualification and application of policies. In all, it had 26 DSC, in which, in general, the main findings on public policies, services, and assistance provided were consistent with the scientific literature. The identification and observation of social representativeness enriched the analysis of the study, by helping the reflexive deepening and the debate, by involving factors related to history, sociocultural context, values and experiential bases. Although the services have been recognized for their quality, they have run into problems due to the precariousness and lack of infrastructure, given the shortage of more financial, physical, material, instrumental, and human resources. At times, the organization and functioning of the systems and services did not meet the real needs of users and their managers, being characterized by inefficient bureaucratic processes and inadequate models of care. Among the access barriers identified, the lack of physical, technological, informational and communicative accessibility stands out. It was possible to observe the absence of practices and policies aimed at the support of the family caregiver and his well-being, as well as the need for qualifying professionals and managers. Ableist behavior and practices emerged in the speeches, as well as the misapplication and disrespect to the guaranteed rights. The weaknesses identified would need to be better analyzed and overcome by the municipal management, in order to re-establish, improve, and consolidate the services implemented in the municipality. This way, it would be possible to have equal conditions and the valorization of the person with disabilities.